Simultaneous Determination of Metformin and Glimepiride in Fixed-Dose Combination Tablets Sold in Pramuka Market using Validated UV Spectrophotometric Method - Zilhadia Zilhadia; Supandi Supandi; Salman Alfarisi (Jurnal Sains Farmasi & Klinis, 2021)
Combination of metformin and glimepiride as a diabetes mellitus drug has recently shown significant increase due to its benefits in improving patient compliance and offering cost effectiveness. This study aimed at analyzing metformin-glimepiride in fixed dose combinations purchased at Pramuka Market (the largest drug market in Jakarta) using validated simultaneous UV-spectrophotometry. The maximum wavelength of metformin and glimepiride is 237 nm and 228 nm respectively. The validation result of metformin and glimepiride at concentration range of 2-8 µg/mL and 5-17 µg/mL showed Linearity with 0.9999 and 0.9996, LOD values with 0.0962 µg/mL and 0.2954 µg/mL, LOQ values with 0.3208 µg/mL and 0.9846 µg/mL, and recovery (accuracy test) with 99.72% ± 1.88% to 103.86 ± 0.87%, respectively. The Relative Standard Deviation (RSD) as the precision test indicator for both drugs was less than 2%. The level of Metformin-glimepiride fixed-dose combination purchased at Pramuka Market was about 96.15% ± 3.56% to 102.71% ± 1.50%. The conclusion of this study showed that the level of metformin-glimepiride sold in the Pramuka market met the requirements